2018
DOI: 10.1039/c8cc02459f
|View full text |Cite
|
Sign up to set email alerts
|

Stable lead(ii) boroxides

Abstract: The first examples of lead(ii) boroxides, [Pb(OB{CH(SiMe3)2}2)2] (1) and [{N^C}PbOB{CH(SiMe3)2}2] (5; N^C = 2-Me2NCH2C6H4), were prepared via simple protocols. These structurally characterised compounds are stable and, unlike lead(ii) alkoxides and siloxides, do not trigger uncontrolled formation of lead(ii) oxoclusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…These reactions afford the target metallylenes [(HCDippN) 2 BO] 2 E in good yield [ 4 : E=Ge (86 %), 5 : E=Sn (88 %), 6 : E=Pb (78 %); Scheme ]. 5 is characterized by a 119 Sn{ 1 H} signal at δ Sn =−109.0 ppm, which is downfield shifted from those of [{(Me 3 Si) 2 HC} 2 BO] 2 Sn ( δ =−186 ppm) and [(2,6‐Dipp 2 C 6 H 3 )O] 2 Sn ( δ =−289.7 ppm) . A similar trend is observed for 6 : the 207 Pb{ 1 H} NMR signal (δ Pb =1885 ppm) is shifted downfield compared to those of [{(Me 3 Si) 2 HC} 2 BO] 2 Pb ( δ =1805 ppm) and [(2,6‐Dipp 2 C 6 H 3 )O] 2 Pb ( δ =1070 ppm)…”
Section: Methodsmentioning
confidence: 99%
“…These reactions afford the target metallylenes [(HCDippN) 2 BO] 2 E in good yield [ 4 : E=Ge (86 %), 5 : E=Sn (88 %), 6 : E=Pb (78 %); Scheme ]. 5 is characterized by a 119 Sn{ 1 H} signal at δ Sn =−109.0 ppm, which is downfield shifted from those of [{(Me 3 Si) 2 HC} 2 BO] 2 Sn ( δ =−186 ppm) and [(2,6‐Dipp 2 C 6 H 3 )O] 2 Sn ( δ =−289.7 ppm) . A similar trend is observed for 6 : the 207 Pb{ 1 H} NMR signal (δ Pb =1885 ppm) is shifted downfield compared to those of [{(Me 3 Si) 2 HC} 2 BO] 2 Pb ( δ =1805 ppm) and [(2,6‐Dipp 2 C 6 H 3 )O] 2 Pb ( δ =1070 ppm)…”
Section: Methodsmentioning
confidence: 99%
“…16 We have also shown that [Pb II ]boryloxides could be obtained as the two-coordinate [Pb(OB{CH(SiMe3)2}2)2] or as the three-coordinate [{2-Me2NCH2C6H4}PbOB{CH(SiMe3)2}2] bearing a bidentate organoligand. 17 Yet, beyond β-diketiminates [3][4][5][6][7][8][9][10][11][12][13][14][15] and bulky terphenyls, [18][19][20] the number of ligands suited to the design of heteroleptic low coordinate lead(II) complexes remains limited. [21][22][23][24][25] In particular, the implementation of potentially bidentate alkoxides for the preparation of soluble heteroleptic lead(II) species only includes a handful of examples, 16,24,26 even if homoleptic [Pb(OR)2]n and [Pb(μ2-OR)N(SiMe3)2]2 alkoxides have been known for some time.…”
Section: Aminofluoroalkoxide Amido and Boryloxo Lead(ii) Complexes † ‡mentioning
confidence: 99%
“…Complex 3, a colourless solid that melts at 128 °C and decomposes irreversibly at 150 °C, is a rare example of stable lead(II) boryloxide. 17 It exhibits good solubility in most common organic solvents, including hydrocarbons. Colourless single crystals suitable for X-ray diffraction analysis were grown from a concentrated petroleum ether solution stored at -43 °C.…”
Section: Aminofluoroalkoxide Amido and Boryloxo Lead(ii) Complexes † ‡mentioning
confidence: 99%
See 2 more Smart Citations